2016
DOI: 10.1016/j.amjms.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin Treatment on Fluid and Electrolyte Balance in Diabetic Rats

Abstract: Aim This study evaluates the effect of dapagliflozin, a SGLT2 inhibitor, on fluid/electrolyte balance and its effect on urea transporter-A1 (UT-A1), aquaporin-2 (AQP2) and Na-K-2Cl cotransporter (NKCC2) protein abundance in diabetic rats. Methods Diabetes mellitus was induced by injection of streptozotocin into the tail vein. Serum Na+, K+, Cl− concentration, urine Na+, K+, Cl− excretion, blood glucose, urine glucose excretion, urine volume, urine osmolality and urine urea excretion were analyzed after the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Excessive urination is a symptom of diabetes and is due to the inability of the renal tubules to absorb glucose filtered in the glomeruli leading to osmotic diuresis [36]. Similarly, in our study urine volume was significantly increased in diabetic rats compared to control rats.…”
Section: Discussionsupporting
confidence: 77%
“…Excessive urination is a symptom of diabetes and is due to the inability of the renal tubules to absorb glucose filtered in the glomeruli leading to osmotic diuresis [36]. Similarly, in our study urine volume was significantly increased in diabetic rats compared to control rats.…”
Section: Discussionsupporting
confidence: 77%
“…Diabetic patients frequently present with electrolyte abnormalities [12]. The diuretic effects of SGLT2i may influence the serum chloride concentration, but few experimental [13][14][15] and clinical studies [16,17] have deeply evaluated the effects and mechanistic consideration of SGLT2i on the serum chloride levels. The findings of the present study indicate that SGLT2i preserves or enhances the serum chloride concentration in T2DM/ non-HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Na + reabsorption in the PT will switch on compensatory systems in more distally located segments to counteract the proximal Na + loss. A recent study has shown that dapagliflozin treatment upregulated the expression of urea transporter-A1, aquaporin-2, and NKCC2 proteins [1]. However, little is known about the effects of SGLT2 inhibitors on the local and downstream Na + transporters.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that treatment with an SGLT2 inhibitor increases the expression of urea transporter-A1, aquaporin-2 and NKCC2 proteins [1]. However, a systematic analysis of the compensatory mechanisms that regulate renal Na + reabsorption after SGLT2 treatment is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation